2021
DOI: 10.4314/jae.v25i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Adoption Determinants of Adapted Climate Smart Agriculture Technologies Among Smallholder Farmers in Machakos, Makueni, and Kitui Counties of Kenya

Abstract: The study examined the adoption determinants of adapted climate smart agriculture (CSA) technologies among smallholder farmers. A multi-stage sampling procedure was used to select a total sample of 384 households. Percentages and regression were employed in data analysis. The results revealed that 47.4% adapted to climate change using integrated farming system, intercropping, crop rotation and agroforestry. Sex (0.9%), education level (9.2%) significantly influenced adoption of the adaptation strategies. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…According to Moronge and Nyamweya (2019), farm size influences adoption as large land gives space to experiment and practice of innovations. The findings agree with those of Muriithi et al, (2021) who indicated that farmers with larger farms, had a higher likelihood of adopting intercropping and crop rotation than those with smaller farms. The findings further reveal a negative association between farm size and uptake of cereal-legume intercrop and pasture cropping .The findings agree with those by Llones and Suwanmaneepong (2021) that increasing farm size will more likely increase input usage under conventional production among nonadopters thus reducing chances of adopting new innovations.…”
Section: Support Required By Farming Households To Increase Uptake Of...supporting
confidence: 90%
See 1 more Smart Citation
“…According to Moronge and Nyamweya (2019), farm size influences adoption as large land gives space to experiment and practice of innovations. The findings agree with those of Muriithi et al, (2021) who indicated that farmers with larger farms, had a higher likelihood of adopting intercropping and crop rotation than those with smaller farms. The findings further reveal a negative association between farm size and uptake of cereal-legume intercrop and pasture cropping .The findings agree with those by Llones and Suwanmaneepong (2021) that increasing farm size will more likely increase input usage under conventional production among nonadopters thus reducing chances of adopting new innovations.…”
Section: Support Required By Farming Households To Increase Uptake Of...supporting
confidence: 90%
“…Generally, education is believed to increase a farmer's awareness and understanding of new agricultural innovations. Muriithi et al (2021) and Zakaria et al (2020) argue that some technologies are knowledge intensive and require basic education to facilitate use and adoption. Therefore this finding challenges those of (Muriithi et al, 2021) and other earlier empirical evidences (Tokede et al, 2020;Zakaria et al, 2020) that show a positive association between education level and farmers' decision to adopt new innovations.…”
Section: Support Required By Farming Households To Increase Uptake Of...mentioning
confidence: 99%
“…Educated people are also in better position to understand the benefits of cowpea storage both from economic and health perspective and hence tend to use the technology more. This corroborates Muriithi et al, 2021) who found education level to affect adoption of climate smart agriculture technology among smallholder farmers in Machakos, Makueni, and Kitui Counties of Kenya. This is contrary to the assertions of Moussa et.…”
Section: Drivers Of Adoption Of Pics Technology In the Study Areasupporting
confidence: 86%
“…Nonetheless, a higher percentage of farmers-33.3% in aza and 42.7% in Giyani-had no formal education, indicating lower levels of literacy study shows that there are more uneducated farmers in the study area. This should cate the need for a major intervention, as education is believed to improve an individ reasoning capability and increase the awareness of variable technologies that ca adopted [53]. There was high exposure and awareness of climate risks, which implies most farmers in the study areas experienced different agro-ecological zones and cli Table 2 presents the sampled smallholder maize farmers' decision to adopt CSA in Ga-Makanye, Gabaza, and Giyani.…”
Section: Smallholder Maize Farmers' Willingness To Adopt Csa In Ga-ma...mentioning
confidence: 99%